2020
DOI: 10.1016/j.sjbs.2020.07.030
|View full text |Cite
|
Sign up to set email alerts
|

Emerging insights into mitochondria-specific targeting and drug delivering strategies: Recent milestones and therapeutic implications

Abstract: Mitochondria are a major intracellular organelle for drug targeting due to its functional roles in cellular metabolism and cell signaling for proliferation and cell death. Mitochondria-targeted treatment strategy could be promising to improve the therapeutic efficacy of cancer while minimizing the adverse side effects. Over the last decades, several studies have explored and focused on mitochondrial functions, which has led to the emergence of mitochondria-specific therapies. Molecules in the mitochondria are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 58 publications
0
12
0
Order By: Relevance
“…Mitochondria are involved in cancer progression and emerging as a promising therapeutic target for cancer therapy [28]. mtDNA can be released from the mitochondria into the cytoplasm and play a key role in inflammation and immunity [29], suggesting that mtDNA is a promising target for cancer therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondria are involved in cancer progression and emerging as a promising therapeutic target for cancer therapy [28]. mtDNA can be released from the mitochondria into the cytoplasm and play a key role in inflammation and immunity [29], suggesting that mtDNA is a promising target for cancer therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Nanotechnology could help overcome several main limitations of conventional chemotherapy and photodynamic and/or photothermal therapies through tissue/cell-specific targeting, controlled release to specific subcellular organelles, and prolonged half-life in circulation. In view of the aforementioned critical role of mitochondria in controlling the fate of cells and the fact that there are prior comprehensive reviews on mitochondria-targeting materials/molecules [ 36 , 37 , 38 ] and mitochondrial biology [ 38 , 39 ], this mini-review surveys mitochondria-targeting nanoparticle drug delivery and its potential and challenges for advancing photodynamic, photothermal, and chemotherapies.…”
Section: Introductionmentioning
confidence: 99%
“…Dysfunctional mitochondria promotes cancer cell invasion, cancer survival and anticancer drug resistance. Nowadays, mitochondria-targeted drug delivery systems are being mechanised making mitochondria—the prime target of new anticancer drugs 8 . Chen et al 9 reported that Imatinib induces mitochondria-assisted apoptosis and restricts the invasion of pigmented villonodular synovitis cells.…”
Section: Introductionmentioning
confidence: 99%